A new genus of neobatrachian frog from southern Patagonian forests, Argentina and Chile NÉSTOR G. BASSO, CARMEN A. ÚBEDA, MARÍA M. BUNGE & LIZA B. MARTINAZZO (Argentina) - Basso, Néstor G.; Úbeda, Carmen A.; Bunge, María M.; Martinazzo, Liza B. (Zootaxa, 2011)
In 1975 Lynch named a new species of frog based on two specimens from Puerto Eden, Wellington Island, southern Chile, tentatively allocated to the genus Telmatobius. Telmatobius grandisonae Lynch was later included by the same author in his genus Atelognathus. Based on a reappraisal of the type material and the description of the internal and external morphology, karyotype, tadpole morphology and molecular evidence from recently discovered specimens collected at Lago del Desierto, southern Argentina, we describe the monotypic genus Chaltenobatrachus, with Telmatobius grandisonae (Lynch) serving as the type species. Chaltenobatrachus differs from Atelognathus mainly in having a uniform bright green dorsal coloration, with brown to reddish warts; orange iris with gold spots; fingers with interdigital membrane; frontoparietals well developed; small nasals;well ossified sphenethmoid; anteriorly expanded homosternum; skin of tadpole transparent; oral disc with protruding anterior and lateral papillae; diploid number 2n = 32 chromosomes. The genetic distances between Chaltenobatrachus and Atelognathus meet or exceed most other intergeneric comparisons.